2016
DOI: 10.1371/journal.pone.0156158
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Wheat Accessions to the English Grain Aphid Sitobion avenae

Abstract: The English grain aphid, Sitobion avenae, is a major pest species of wheat crops; however, certain varieties may have stronger resistance to infestation than others. Here, we investigated 3 classical resistance mechanisms (antixenosis, antibiosis, and tolerance) by 14 wheat varieties/lines to S. avenae under laboratory and field conditions. Under laboratory conditions, alatae given the choice between 2 wheat varieties, strongly discriminated against certain varieties. Specifically, the ‘Amigo’ variety had the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…The use of combinations of different cultivars of host plants in the field can significantly reduce aphid occurrence ( Ninkovic et al 2002 ). To determine whether a crop cultivar is resistant to aphids, testing is required under changing temperature and humidity conditions similar to those in the field ( Atlıhan et al 2017 ) and during different seasons in field conditions ( Hu et al 2016 ). Such testing is important because interannual variability in antibiosis has been reported ( Hu et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of combinations of different cultivars of host plants in the field can significantly reduce aphid occurrence ( Ninkovic et al 2002 ). To determine whether a crop cultivar is resistant to aphids, testing is required under changing temperature and humidity conditions similar to those in the field ( Atlıhan et al 2017 ) and during different seasons in field conditions ( Hu et al 2016 ). Such testing is important because interannual variability in antibiosis has been reported ( Hu et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Screening cultivars and genetic lineages for resistance to aphids should be the first step of this process. Variability in resistance to aphids has been shown among different cultivars of a same host plant species, including cereals ( Papp and Mesterházy 1996 , Migui and Lamb 2004 , Klueken et al 2008 , Hu et al 2016 , Girvin et al 2017 , Ajmal et al 2018 , Chandrasekhar et al 2018 ). Ancient taxa of the genus Triticum , including einkorn ( Triticum monococcum L.), durum wheat ( Triticum turgidum (L.) ssp.…”
mentioning
confidence: 99%
“…And five in 200 genotypes from the main wheatproducing areas of China were moderately resistant (Zhou et al 2011). Hu et al (2016) detected great differences in the crop yield loss rates and the aphid number ratio of the same germplasm. And yet, some studies have suggested that the aphid number ratio is suitable for the preliminary screening of large quantities of wheat germplasm materials in the field (Zhou et al 2011;Wang et al 2013;.…”
Section: Discussionmentioning
confidence: 96%
“…The wheat aphid, Sitobion avenae , migrates from southern to northern China and causes ~ 10% wheat yield losses every year [12]. Here, we investigated S. avenae wing development and IFM degeneration, and identified some differentially expressed genes pre-/post-migration.…”
Section: Introductionmentioning
confidence: 99%